Neurotransmitter transporter occupancy following administration of centanafadine sustained-release tablets: A phase 1 study in healthy male adults. (February 2023) - Matuskey, David; Gallezot, Jean-Dominique; Nabulsi, Nabeel; Henry, Shannan; Torres, Kristen; Dias, Mark; Angarita, Gustavo A; Huang, Yiyun; Shoaf, Susan E; Carson, Richard E; Mehrotra, Shailly
Background: Centanafadine is an inhibitor of reuptake transporters for norepinephrine (NET), dopamine (DAT) and serotonin (SERT). Aims: This phase 1, adaptive-design positron emission tomography study investigated the occupancy time course of NET, DAT, and SERT and the relationship to centanafadine plasma concentrations. Methods: Healthy adult males received centanafadine sustained-release 400 mg/day for 4 days ( N  = 6) or 800 mg in a single day ( N  = 4). Assessments included safety monitoring; time course of occupancy of NET, DAT, and SERT; and centanafadine plasma concentrations. Results: Transporter occupancy was numerically higher for NET versus DAT or SERT. For NET, estimated (mean ± standard error [SE]) maximal observable target occupancy (TOmax ) and concentration at half maximal occupancy (IC50 ) were 64 ± 7% and 132 ± 65 ng/mL, respectively, for all regions and 82 ± 13% and 135 ± 97 ng/mL after excluding the thalamus, which showed high nonspecific binding. For DAT and SERT, TOmax could not be established and was assumed to be 100%; estimated IC50 (mean ± SE) values were 1580 ± 186 ng/mL and 1, 760 ± 309 ng/mL, respectively. For centanafadine, the estimated in vivo affinity ratio was 11.9 ± 6.0 (mean ± SE) for NET/DAT, 13.3 ± 7.0 for NET/SERT, and 1.1 ± 0.2 for DAT/SERT. DAT and SERT occupancies at a plasma concentration of 1400 ng/mL were estimated to be 47 and 44%, respectively. Conclusions: High occupancy at NET and moderate occupancy at DAT and SERT was observed at peak concentrations achieved following 400 mg total daily doses of centanafadine.